2021
DOI: 10.1155/2021/5510623
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Lymph Node Biopsy Is Feasible in Cervical Cancer Laparoscopic Surgery: A Single-Center Retrospective Cohort Study

Abstract: Background and Objective. Sentinel lymph node (SLN) biopsy efficiency has been confirmed in various solid tumors. This study aimed to assess SLN biopsy feasibility in clinical application and explore how to improve its detection rates and diagnostic accuracy in cervical cancer laparoscopic surgery. Methods. A total of 100 cervical cancer patients undergoing laparoscopic surgery with SLN biopsy were included. Indocyanine green, carbon nanoparticles (CNPs), and a combination of both were used during surgeries. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…There are no adverse reactions reported yet, and the DR is quite high. Data from our hospital showed that the combination of CNP and ICG resulted a higher BDR of SLN in cervical and endometrial cancer comparing to CNP or ICG alone (p<0.05) (45,46).…”
Section: The Technique Advances Of Slnm Detection Methodsmentioning
confidence: 94%
“…There are no adverse reactions reported yet, and the DR is quite high. Data from our hospital showed that the combination of CNP and ICG resulted a higher BDR of SLN in cervical and endometrial cancer comparing to CNP or ICG alone (p<0.05) (45,46).…”
Section: The Technique Advances Of Slnm Detection Methodsmentioning
confidence: 94%
“…[17][18][19] Recently, an increasing number of studies have focused on fluorescent indocyanine green (ICG) applied for SLN mapping of cervical cancer as it could improve SLN detection. 20,21 Hou et al 22 reported that the bilateral detection rate was significantly higher for combined ICG and CNP than CNP alone (75.3% vs 54.3%). However, ICG requires special fluorescence laparoscopy, whereas compared to traditional mapping techniques, CNS has more advantages, including no radiation exposure, no pain, no need for special instruments during operation, and a much lower cost.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent dye indocyanine green (ICG), a safe and effective agent for SLNM, has emerged as the most recommended tracer for intraoperative detection of SLN in endometrial cancer owing to its higher sensitivity and specificity compared with conventional tracers (blue dye and radiotracer) [15,16,17] . In fact, Backes et al found that in contrast with ISB, ICG was conspicuously more effective in detecting SLN (ICG's detection rate is 83% while ISB's is 64%) [18] .…”
Section: Injection Tracermentioning
confidence: 99%